Keputusan Karier Siswa SMA ditinjau dari Teori Cognitive Information Processing (CIP) - Kholiza Fitri, Nur; Firman; Netrawati (CV. ITTC INDONESIA, 2024)
Career decisions are one of the critical challenges faced by high school students, especially when they are in the transition period from formal education to the world of work or higher education. However, many students still experience confusion and lack confidence in making career decisions, which has the potential to hinder their future development. This research aims to analyze high school students' career decisions based on three aspects of Cognitive Information Processing theory, namely Knowledge Domain, Decision Making Skill Domain, Executive Processing Domain. This research method is quantitative, the research sample is high school students with a population of 243 people, a sample of 151 people was obtained using the Stratified Random Sampling method. The instrument is a career decision questionnaire. Data is analyzed using percentage and frequency distribution techniques. The results of the research found that in the Knowlege Domain aspect some students were in the high category with 104 students out of the total, this indicates that students have good knowledge about careers, in the Decision Making Skill Domain aspect there were also 99 students in the high category, which means decision making skills. students are good and the Executive Processing Domain aspect is in the high category with 116 students, which means the implementation of student decisions is good. In conclusion, these findings indicate that the majority of students have adequate knowledge, skills and execution abilities in making career decisions. However, there are a number of students who are still in the low category, indicating the need for career guidance interventions to ensure that all students are able to make optimal career decisions and in line with their potential.